2006
DOI: 10.1029/2006gl025966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interplanetary shock strengths and orientations on storm sudden commencement rise times

Abstract: [1] We make a statistical survey of interplanetary (IP) shocks and storm sudden commencements (SSCs) observed between 1995 and 2004. We find that 75% of SSCs are associated with shocks, consistent with previous work. We use this survey to investigate the effect of the interplanetary shock strength and orientation on the SSC rise time. We find that the higher the speed of an IP shock, the less time it takes to sweep by the magnetosphere, and thus the shorter the rise time of the corresponding SSC. The orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
53
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 9 publications
(10 reference statements)
29
53
0
1
Order By: Relevance
“…The field rise time is about 4-5 min at all stations, which is very close to the values observed for shocks nearly perpendicular to the X GSM direction (e.g. Wang et al, 2006). However, as we have noted in Sect.…”
Section: Shock Front Orientation and Time Delayssupporting
confidence: 48%
“…The field rise time is about 4-5 min at all stations, which is very close to the values observed for shocks nearly perpendicular to the X GSM direction (e.g. Wang et al, 2006). However, as we have noted in Sect.…”
Section: Shock Front Orientation and Time Delayssupporting
confidence: 48%
“…According to Fig. 3 of Wang et al (2006), a substantial increase in the rise time seems to occur for events with a normal angle of less than ~150°. Thus, the lack of a rise-time normal-angle dependence in our events could be because of the small normal angles from the Sun-Earth line.…”
Section: Shock Orientationmentioning
confidence: 99%
“…Such a difference was also seen in the analysis of Takeuchi et al, and the quasi-linear polarization nature of the changes in the magnetic field at the shocks may again introduce large uncertainties in the coplanarity method. According to Araki et al (2004) and Wang et al (2006), a larger shock normal angle from the Sun-Earth line leads to a more gradual SC because the shock sweeping time across a geoeffective length [30 R E by Araki et al (2004)] becomes longer. However, the SYM-H rise time in our events does not show a clear dependence on the shock normal angle (Table 1).…”
Section: Shock Orientationmentioning
confidence: 99%
“…The time duration of SI depends on the following: the time taken by the shock front or discontinuity to sweep the geoeffective distance along the magnetosphere, the thickness of the shock front or the discontinuity in the solar wind, inertia of the magnetospheric plasma, and the broadening of the wave front during the passage through the magnetosphere (Nishida 1966). Wang et al (2006) statistically investigated the effect of the interplanetary shock strength and orientation on SI rise time and found that oblique shocks result in a longer rise time of SIs. Nishida and Jacobs (1962) noticed a similarity between positive and negative SIs and claimed that any theory of positive impulse (SI + ) should be able to explain the phenomenon of negative impulse (SI − ) in an opposite sense.…”
Section: Introductionmentioning
confidence: 99%
“…However, not many studies have been carried out to investigate the LT variation for an individual SI. Gaining an understanding of this is important, as the results may differ for various SI events because the geomagnetic field response to SIs strongly depends on factors such as the orientation and magnitude of the interplanetary magnetic field (Wing and Sibeck 1997;Lee and Lyons 2004), orientation of shocks/discontinuities (Takeuchi et al 2002b;Wang et al 2006), the value of pressure before disturbance, and the change in pressure amplitude (Borodkova et al 2006). Therefore, any statistical studies performed without consideration of these aspects may be unable to provide a true picture of the LT variation, which indicates the importance of case studies.…”
Section: Introductionmentioning
confidence: 99%